The Effect of Influencer, Promotion and Brand Awareness on Purchase Decision of Skincare Product The Originote at Belia Cosmetics Store Surabaya - Safa Sarah Azizah; Ani Wulandari; Elok Damayanti; Chriestine Ayu Ashari (LPPM of NAROTAMA UNIVERSITY, 2025)
This research aims to analyze the effect of Influencer, Promotion and Brand Awareness on Purchase Decision of Skincare Product The Originate at Belia Cosmetics Store Surabaya. This study uses quantitative research methods. The sampling technique for this study was using Purposive Sampling to determine the sample and involved respondents from consumers at Belia Cosmetics Store Surabaya who used skincare product The Originote, there were usable 111 in this study. This study uses primary data and secondary data. The type of research used is quantitative research, using the Multiple Linear Regression data analysis method through the IBM SPSS version 26 application. The results showed that Influencer (X1), Promotion (X2), Brand Awareness (X3) partially or simultaneously had a positive and significant effect on Purchase Decision. Influencer (X1) with a t-count value of 4.882 and a sig. 0,000. Simultaneously, the variables Influencer (X1), Promotion (X2), Brand Awareness (X3) have a positive and significant effect on Purchase Decision with an f-count value of 62.755 with a sig. 0,000. This study are limited to Consumen of Skincare product at Belia Cosmetics Surabaya. Besides, the focus of this stud is to analyze Influencer, Promotion and Brand Awarneess on Purchase Decision